Antiinflammatory and Anticancer Properties of Grewia asiatica Crude Extracts and Fractions: A Bioassay-Guided Approach. (28th March 2022) - Qamar, Muhammad; Akhtar, Saeed; Barnard, Ross T.; Sestili, Piero; Ziora, Zyta M.; Lazarte, Claudia E.; Ismail, Tariq
Abstract : The study was an extension of our earlier work on antiinflammatory and anticancer properties of G. asiatica fruit. We aimed to develop a bioassay guided multistep purification technique for producing bioactive fractions of G. asiatica crude extracts. Dried fruit powder was sequentially fractionated with 100% dichloromethane, 100% methanol (MeOH), and 50% MeOH. Active extracts were subjected to liquid-liquid partitioning followed by subfractionation using RP-HPLC. Antioxidant, antiinflammatory, and anticancer activities of the fruit extracts, and their potent fractions were evaluated in vitro, while identification of compounds from the bioactive fractions was performed by ESI-MS/MS analysis. The amount of the identified compounds present was confirmed using external standards adopting a simple, accurate, and rapid analytical HPLC method. The results showed that 100% and 50% MeOH extracts possessed bioactivity; one of which (the 50% MeOH extract) displayed potent activity in all in vitro bioassays. MeOH extract (50%) derived fraction C and hydroalcoholic fraction 5 (GAHAF5) were observed to possess higher antioxidant, antiinflammatory, and in vitro anticancer activity. IC50 of GAHAF5 against MCF-7, HEp-2, and NCI-H522 cancer cells was recorded as 26.2, 51.4, and 63 μ g/mL, respectively. ESI-MS/MS and HPLC analysis identified catechin, chlorogenic acid, caffeic acid, and morin as potential bioactive compounds in the GAHAF5 fraction with concentrations of 1230, 491, 957, and 130 μ g/g, respectively. The findings indicated that G. asiatica bioactive fractions possessed antiinflammatory activity in vitro and were cytotoxic against breast cancer, lung cancer, and laryngeal cancer cell lines.